Thoracic Ultrasound: A Narrative Literature Review - Atikanur; Indi Esha (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Ultrasonography (USG) is useful in diagnosing abnormalities in the thoracic area, such as pleural effusion, pneumothorax, consolidation, atelectasis, pulmonary edema, etc. The advantages of thoracic ultrasound are low cost, non-radiation, non-invasive, easy to carry, short examination time, and a dynamic aspect that can be seen during the examination. Thoracic ultrasound can be used to guide thoracentesis procedures, chest tube placement, and aspiration of lung abscesses. Ultrasound can be substituted as a computed tomography scan (CT-Scan) as a guide for aspiration and biopsy of the lung parenchyma, pleura, and chest wall. Portable and compact ultrasonography provides the opportunity for ultrasound examinations to become a routine part of an examination, like a stethoscope. Ultrasonography also has limitations in patients with subcutaneous emphysema, peripheral edema, and obesity. Ultrasound examination is very dependent on the experience and abilities of the operator.